Influence of Deposition Temperature on the Structure and Current-Carrying Friction Performance of Cu Films by DC Magnetron Sputtering Technology - Hao Zhang; Kai Le; Chen Wang; Jianbo Sun; Shusheng Xu; Weimin Liu (Lubricants, 2022)
The structure and morphology of Cu films deposited by DC magnetron sputtering on silicon and stainless-steel substrates at different deposition temperatures of −140 °C, −95 °C, −55 °C, 25 °C (RT), 50 °C, and 200 °C were investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM), and atomic force microscopy (AFM). It was found that all Cu films presented strong orientation of the (111) and (200) peaks. The Cu films deposited at low temperatures (lower than −55 °C) showed the bilayer structures, in which the upper layer appeared to be a loose and porous structure and the lower layer near the substrate had a fine and dense structure that consisted of small grains. In addition, the Cu films deposited at low temperatures could be observed a large roughness. The roughness tended to decline and then increase with the rising of deposition temperature. The ball-on-disc reciprocating sliding tribometer was employed to evaluate the tribological behaviors of the Cu films at current-carrying levels of 0 A, 0.5 A, and 1.0 A. The results revealed that the Cu films deposited at low temperatures exhibited outstanding current-carrying friction performance and low electrical contact resistance (ECR), peeling only at 0.5 A and 1.0 A. Nevertheless, the Cu films deposited at the relatively high temperature exhibited oxidative wear caused by electric arc ablation at 0.5 A and 1.0 A. Additionally, the wear mechanism was discussed in terms of the structure and morphology of the wear track and formation of the tribo-film.